Determinants of marginalization and inequitable maternal health care in North–Central Vietnam: a framework analysis - Binder-Finnema, Pauline (Glob Health Action, 2015)
BACKGROUND: Vietnam has achieved great improvements in maternal healthcare outcomes, but there is evidence of increasing inequity. Disadvantaged groups, predominantly ethnic minorities and people living in remote mountainous areas, do not gain access to maternal health improvements despite targeted efforts from policymakers. OBJECTIVE: This study identifies underlying structural barriers to equitable maternal health care in Nghe An province, Vietnam. Experiences of social inequity and limited access among child-bearing ethnic and minority women are explored in relation to barriers of care provision experienced by maternal health professionals to gain deeper understanding on health outcomes. DESIGN: In 2012, 11 focus group discussions with women and medical care professionals at local community health centers and district hospitals were conducted using a hermeneutic–dialectic method and analyzed for interpretation using framework analysis. RESULTS: The social determinants ‘limited negotiation power’ and ‘limited autonomy’ orchestrate cyclical effects of shared marginalization for both women and care professionals within the provincial health system’s infrastructure. Under-staffed and poorly equipped community health facilities refer women and create overload at receiving health centers. Limited resources appear diverted away from local community centers as compensation to the district for overloaded facilities. Poor reputation for low care quality exists, and professionals are held in low repute for causing overload and resulting adverse outcomes. Country-wide reforms force women to bear responsibility for limited treatment adherence and health insight, but overlook providers’ limited professional development. Ethnic minority women are hindered by relatives from accessing care choices and costs, despite having advanced insight about government reforms to alleviate poverty. Communication challenges are worsened by non-existent interpretation systems. CONCLUSIONS: For maternal health policy outcomes to become effective, it is important to understand that limited negotiation power and limited autonomy simultaneously confront childbearing women and health professionals. These two determinants underlie the inequitable economic, social, and political forces in Vietnam’s disadvantaged communities, and result in marginalized status shared by both in the poorest sectors.